2012
DOI: 10.1007/s00248-012-0132-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Root Bacterial Communities Associated to Two Different Development Stages of Canola (Brassica napus L. var oleifera) Evaluated through Next-Generation Sequencing Technology

Abstract: Crop production may benefit from plant growth-promoting bacteria. The knowledge on bacterial communities is indispensable in agricultural systems that intend to apply beneficial bacteria to improve plant health and production of crops such as canola. In this work, the diversity of root bacterial communities associated to two different developmental phases of canola (Brassica napus L.) plants was assessed through the application of new generation sequencing technology. Total bacterial DNA was extracted from roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…No significant effects of crop sequence shown on shoot growth parameters (SPAD value, LAI, and biomass yield) and final grain yield suggest that the expected biopore effects on overall crop performance might be more vividly shown under stress condition (Volkmar 1996;Gaiser et al 2012). More importantly, understanding 4 Root length (km m −2 ) inside (a) and outside (b) of biopores beneath 45 cm of soil depth as affected by crop sequence (chicorywheat and tall fescue-wheat) and growth stage (tillering, booting, anthesis, and milk) in 2012.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…No significant effects of crop sequence shown on shoot growth parameters (SPAD value, LAI, and biomass yield) and final grain yield suggest that the expected biopore effects on overall crop performance might be more vividly shown under stress condition (Volkmar 1996;Gaiser et al 2012). More importantly, understanding 4 Root length (km m −2 ) inside (a) and outside (b) of biopores beneath 45 cm of soil depth as affected by crop sequence (chicorywheat and tall fescue-wheat) and growth stage (tillering, booting, anthesis, and milk) in 2012.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, a novel visual approach has also shown that roots elongating inside biopores cross the pore walls in deep soil horizons (Athmann et al 2013), thus can re-explore the bulk soil. Improved water (Gaiser et al 2012) and N uptake (Volkmar 1996) by wheat as a function of pore-assisted root growth suggest that plants are capable of utilizing subsoil resources when accessible . Increased plant P availability (Barej et al 2014) and microbial activity (Kuzyakov et al 2007;Uksa et al 2014) in zones adjacent to large sized biopores also indicate that the biologically created pores might be hotspots for nutrient acquisition (Kautz et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Hong et al (2015) found that the variable degree of heavy metals in the soil in iron mining areas increased bacterial alpha diversity and changed the dominant genera. Cadmium pollution of soil reportedly can change the taxonomic diversity and functionality of the microbial communities, and further affect soil quality and plant growth (de Campos et al 2013;Hill et al 2000;Li et al 2014;Tipayno et al 2011).…”
mentioning
confidence: 99%
“…Many studies have verified that some certain oilseed rape varieties had tolerance of Cd and possessed the ability to accumulate it (Dechun and Wong 2002;Ru et al 2004;Su et al 2009). However, studies regarding interactions between microorganisms and B. napus in soil polluted with heavy mental are still at a preliminary stage (Germida et al 1998;Dunfield and Germida 2003;Farina et al 2012;Croes et al 2013;de Campos et al 2013). So far, no study has revealed the effects of varying Cd levels on both bacterial and fungal diversity in the soil cropped with oilseed rape via NGS technology.…”
mentioning
confidence: 99%
“…Bacterial communities can be characterized by metagenomics approaches as e.g. applied to monitor changes of root bacterial communities associated to two different development stages of canola (Brassica napus L. var oleifera; de Campos et al, 2013). Studies focusing on isolation of plant growth-promoting bacteria are also often performed, e.g.…”
mentioning
confidence: 99%